IPM-based Animation for Fall Armyworm: A Multi- Institutional and Virtual International Collaboration Using the Scientific Animations Without Borders (SAWBO) Platform. (1st October 2018) - Bello-Bravo, Julia; Huesing, Joseph; Boddupalli, Prasanna; Goergen, Georg; Eddy, Regina; Tamò, Manuele; Pittendrigh, Barry Robert
Rapid dissemination of critical and accurate information to low-resource and poorly literate people in crisis situations has long been a challenge. Historically, print media as well as radio and television have served as major delivery channels. With the advent of cellphones, SMS (texting), and the Internet, these digital technologies now afford enhanced opportunities for reaching this poorly literate, low-resource client group quickly and efficiently. Here, we describe a two-step, rapid response approach to the Fall Armyworm (Spodoptera frugiperda), an invasive noctuid pest newly causing havoc on maize production in Africa and Asia. First, we developed a science-based, animated video – now being localized further into various languages across Africa and Asia – intended to aid semi-literate, smallholder farmers in identifying and scouting for fall armyworm effectively. Second, we made the animation easily available for (re)distribution in affected areas via the Internet and copying/sharing with Bluetooth®, thereby exponentially increasing the animation's reach across a wide spectrum of diverse languages and literacy levels. In this way, this form of asymmetrical communication hybridizes and combines the educational qualities of print dissemination with the range of radio/television delivery. An urgent need now exists to place the existing mobile ESD FAW animation into as many local languages as needed/possible to improve management of this pest. Such language variants will also increase the usefulness of the FAW animation for governments, intergovernmental institutions, non-government organizations, and civil society groups intent of working with farmers in Africa (and Asia) as it pertains to FAW IPM. The USAID, CIMMYT, IITA, and SAWBO teams will continue to foster awareness around mobile ESD as a FAW resource through each of their respective networks, but we also encourage other research and development organizations to do the same. More broadly, there is also the need to develop and disseminate further SAWBO mobile ESD animations on other aspects of FAW management to assist farmers in their attempts to control this pest. Making sure that target audiences have access to this animation, and any future animations, is undoubtedly a considerable challenge. It will be critical to inform intergovernmental, governmental, and non-governmental organizations, working directly or indirectly with farmers, that this resource exists, such that they can be the direct conduit to its deployment in the field. Thus, this (and any future FAW) animation(s) represent(s) a supporting tool for other organizations to use. It will also require that they develop localized pathways for deployment. However, it is important to note that training local educational deployment agents (e.g., extension agents) in the use of the SAWBO Deployer App allows for a highly effective approach to make SAWBO animations available for deployment with farmers in real time as new animations and language variants become available.